Preparación para la vida cotidiana con la mayor independencia posible para la inclusión social de los estudiantes con discapacidad intelectual severa en la unidad de educación especial fiscal Dr. Fernando López Lara - Villamar Gilces, Julio (2017)
One of the challenges of educational institutions specialized in the Ecuador, is the achieve greater efficiency in the learning and development of adaptive, labor skills that contribute to the development of the skills of young people with severe intellectual disabilities, therefore this research is focused on the development of this theme and takes as Dr. Fernando intentionally probabilistic shows a group of young people with intellectual disabilities severe educational unit Lopez Lara, to delve into methodological theoretical considerations and practices of the preparation for the life of young people with disability as a dependent variable, dimensions and indicators, that is characterized the initial situation of this variable from its performance parameters in four dimensions: development of skills of the adaptive behavior of studied young, specialized school the family of studied young people, as well as occupational skills and social participation of young people with severe intellectual disabilities studied. A methodological framework of descriptive, applied from a mixed approach, through the implementation of theoretical, empirical and statistical methods. We designed a strategy that included foundations, qualities and requirements for its implementation, stages and activities…….